2022
DOI: 10.3389/fonc.2022.848036
|View full text |Cite
|
Sign up to set email alerts
|

5-Aminolevulinic Acid False-Positive Rates in Newly Diagnosed and Recurrent Glioblastoma: Do Pseudoprogression and Radionecrosis Play a Role? A Meta-Analysis

Abstract: BackgroundSeveral studies have confirmed the impact of 5-aminolevulinic acid (5-ALA) on the extent of resection in newly diagnosed glioblastoma (GBM). However, there are controversies on the 5-ALA fluorescence status in recurrent GBM surgery, with specific reference to pseudoprogression or radionecrosis; therefore, the safety and accuracy of surgical planning in 5-ALA-assisted procedures in the recurrent context are still unclear.Materials and MethodsThis is a systematic review and meta-analysis of comparative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
(25 reference statements)
1
6
0
Order By: Relevance
“…Notably, all of these conditions share a conspicuous number of immune cells which, as mentioned before, can display fluorescence due to 5-ALA uptake and metabolism. In addition, the macroscopic fluorescence in bacterial brain abscesses could be explained by the bacteria capability to elaborate porphyrin precursors, since they are useful cofactors for their growth [ 19 , 20 , 21 ] ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, all of these conditions share a conspicuous number of immune cells which, as mentioned before, can display fluorescence due to 5-ALA uptake and metabolism. In addition, the macroscopic fluorescence in bacterial brain abscesses could be explained by the bacteria capability to elaborate porphyrin precursors, since they are useful cofactors for their growth [ 19 , 20 , 21 ] ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 5-ALA increased the accumulation of intracellular PpIX in GBM cells, which is consistent with several other studies. 40,41 There is a close relation between 5-ALA-induced PpIX accumulation and tumor cell cytotoxicity and apoptosis. It has been suggested that the accumulated PpIX enhances cytotoxic and apoptosisinducing effects through regulation of reactive oxygen species generation, cytokine and chemokine production, and increasing p53 expression level as well as Bax/Bcl-2 ratio.…”
Section: The Effects Of Aprepitant 5-ala and Their Combination On Flu...mentioning
confidence: 99%
“…Another challenge is the non-specific accumulation of PpIX in nontumor tissues. PpIX fluorescence in non-neoplastic tissues has been reported in regions of inflammatory infiltration around HGG, reactive gliosis in patients receiving adjuvant therapy for recurrent HGG, and LNs accompanied by lymph follicles [ 13 , 15 , 55 , 111 , 120 ]; peritumoral inflammatory conditions and elevated reactive mitotic activity could provide an explanation for the false-positive findings [ 55 ]. Some researchers have suggested that PpIX deposition in inflammatory lesions is associated with intracellular iron metabolism [ 107 , 108 ]; however, the precise mechanism is unknown.…”
Section: Challenges In 5-ala Pddmentioning
confidence: 99%
“…Especially in the case of 5-ALA PDD of recurrent HGG, critical interpretation of intraoperative fluorescence is required because non-specific PpIX fluorescence can be seen in inflammatory lesions [ 55 , 120 ]. Additionally, in other neoplasms, it is important to reduce the false-positive rate owing to non-specific PpIX accumulation to improve the performance of 5-ALA PDD.…”
Section: Challenges In 5-ala Pddmentioning
confidence: 99%